2006
DOI: 10.1021/ac052056n
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Diffusion of Molecules into Individual Polymer Particles by Confocal Raman Microscopy

Abstract: Raman microscopy is a powerful method for providing spatially resolved, chemically selective information about the composition of materials. With confocal collection optics, the method is well suited to the analysis of small particles in contact with liquid solutions. In this work, the transport of an organic solvent component into small polystyrene particles is investigated. An inverted confocal Raman microscope is used to acquire spectra from individual 75-microm polystyrene particles in contact with acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Within this framework, we have shown that EIS provides a powerful alternative tool for exploring dynamical aspects and elucidating the magnitude of the molecular transport process occurring at macromolecular interfaces and polymer thin films. 37,38 ACKNOWLEDGMENT C.A.G. gratefully acknowledges the Comisió n de Investigaciones Científicas y Té cnicas Buenos Aires (CICBA) for his position as a member of the Carrera del Investigador Científico.…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, we have shown that EIS provides a powerful alternative tool for exploring dynamical aspects and elucidating the magnitude of the molecular transport process occurring at macromolecular interfaces and polymer thin films. 37,38 ACKNOWLEDGMENT C.A.G. gratefully acknowledges the Comisió n de Investigaciones Científicas y Té cnicas Buenos Aires (CICBA) for his position as a member of the Carrera del Investigador Científico.…”
Section: Discussionmentioning
confidence: 99%
“…For Raman confocal microscopy, 10 -20 µm meibum films were created by application of 10 µl of 10 mg/ml meibum in chloroform to a coverslip on a 1 mm x 7 mm flow channel (82) followed by drying under nitrogen and then briefly under vacuum with thickness between coverslip-meibum and meibum-buffer interfaces estimated by incident laser beam reflection. The Raman microscopic probe (83,84) has a depth resolution of ±1.2 µm (FWHM), a diameter of ~500 nm, and a probe volume of ~500 fL which is well-matched to the meibum film deposited on the coverslip interface. For analyses, the probe was brought to 1.5 µm below the meibum-buffer interface with spectra collected at a laser power of 100 mW with an integration time of two minutes.…”
Section: -(O-oleoyloxy)hexadecanoicmentioning
confidence: 99%
“…Numerous workers have confirmed the benefits of using immersion objectives to depth profile complicated materials ranging from polymers and paper products to human skin. [29][30][31][32][33][34][35][36][37][38][39][40] As well as reducing the depth-scale compression, the oil has an additional beneficial effect of wetting out particle/air boundaries in porous, highly scattering particulate coatings, improving transparency and permitting confocal profiling of samples that would be opaque to a dry objective. 28 Nonetheless, a significant mismatch between the index of the coupling oil and the sample will result in a slight axial shift and distortion in the shape of individual layers, manifested by an attenuation that increases with depth.…”
Section: Avoiding Spherical Aberration and Depth Scale Compressionmentioning
confidence: 99%